2020
DOI: 10.4103/aam.aam_35_19
|View full text |Cite
|
Sign up to set email alerts
|

Role of serum ferritin as a prognostic marker in acute ischemic stroke: A preliminary observation

Abstract: Background: Acute ischemic stroke is an important cause of morbidity and mortality. Search has been on to find out the factors which can help in formulating the prognosis of acute ischemic stroke. One of the prognostic indicators, which has gained great clinical interest in recent times, is serum ferritin. Aims: To assess the serum ferritin levels in patients with acute ischemic stroke and to study the role of serum ferritin as a prognostic marker in these patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
(31 reference statements)
1
9
0
Order By: Relevance
“…Ferritin reduction is related to cerebral ischemia-induced hippocampal ferroptosis [ 112 ]. A study found that increased serum ferritin levels correlate with severity of stroke and size of the lesion [ 113 , 114 ]. Additionally, elevated serum ferritin levels at admission were associated with post-stroke depression [ 115 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ferritin reduction is related to cerebral ischemia-induced hippocampal ferroptosis [ 112 ]. A study found that increased serum ferritin levels correlate with severity of stroke and size of the lesion [ 113 , 114 ]. Additionally, elevated serum ferritin levels at admission were associated with post-stroke depression [ 115 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another study in 79 North Indian AIS patients showed ferritin >370 ng/mL significantly increased the risk of having bad 6-month outcome (defined as mRS ≥2) [14]. Another two observational studies performed Pearson’s r correlation and found admission serum ferritin level was correlated with Canadian stroke scale scores on the 6th day ( p < 0.001) [16] and mRS score after 4 weeks ( p = 0.00001) [17], which can be used as a prognostic marker in AIS patients. Controversially, higher admission serum ferritin could not predict 3-month functional disability assessed by the Functional Independence Measure and Functional Ambulation Scale in 62 AIS patients [18].…”
Section: Discussionmentioning
confidence: 99%
“…However, whether elevated serum ferritin is related to poor outcome of AIS patients remains controversial. Some studies reported elevated serum ferritin is related to poorer prognosis of ischemic stroke [14][15][16][17], whereas other study found higher serum ferritin could not predict functional disability at 3 months [18]. Besides, high iron status may have a cooperative effect on the process of cell damage and dysfunction induced by hyperglycemic status [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, plasma endostatin [ 76 ], brain natriuretic peptide (BNP) [ 77 , 78 ], serum ferritin [ 79 , 80 ], plasma fibroblast growth factor [ 81 ], plasma trimethylamine-N-oxide content [ 82 ], hypersensitive cardiac troponin [ 83 ], coagulant-related factors C-type lectin receptor 2 and anti-phosphatidylserine [ 84 , 85 ], circulating IGF-1 [ 86 ], plasma lipid metabolism [ 87-89 ], plasma D-dimer [ 90 ] and other biochemical metabolites may be related to the prognosis of AIS. For example, Yang et al prospectively included patients with AIS pneumonia associated with atrial fibrillation (AF) and found significant increases in 3-month mortality and severe residual risk associated with high D-dimer levels and pneumonia AIS, suggesting that plasma D-dimer has prognostic value [ 91 ].…”
Section: Effect Of Blood Biomarkers On Prognosis Of Aismentioning
confidence: 99%